The American Review of International Arbitration / 1995/ Vol.6 No.3 - Columbia University (Parker School Of Foreign And Comparative Law, 1995)
The Uncitral Model Law in State and Federal Courts: The Case of Waiver, Competition Law Issues in International Commercial Arbitration: An Arbitrator's Viewpoint.